Investigation of Some Morphological Traits of Hair Goats in Under Breeder Conditions in Isparta Province - Mustafa Varol; Sibel Alapala Demirhan (Turkish Journal of Agriculture: Food Science and Technology, 2022)
In this study, the morphological body characteristics of hair goats bred in Isparta province, such as withers height, back height, rump height, chest width and body length, were investigated. The animal material of the study consisted of 45 hair goats in 3 farms in total, in lowland conditions, high pasture and highland conditions in the center of Isparta. In the examinations, it was found that the measurements of the males were longer than the measurements of the females in terms of withers, back and rump height, chest circumference and body length, respectively. While the difference was found to be significant in terms of withers height, back height, rump height, and body length (p